CRISPR Activation Enhances In Vitro Potency of AAV Vectors Driven by Tissue-Specific Promoters - McDougald, Devin S. (Mol Ther Methods Clin Dev, 2019)
Validation of gene transfer vectors containing tissue-specific promoters in cell-based functional assays poses a formidable challenge for gene therapy product development. Here, we describe a novel approach based on CRISPR/dCas9 transcriptional activation to achieve robust transgene expression from transgene cassettes containing tissue or cell type-specific promoters after infection with AAV vectors in cell-based systems. Guide RNA sequences targeting two promoters that are highly active within mammalian photoreceptors were screened in a novel promoter activation assay. Using this screen, we generated and characterized stable cell lines that co-express dCas9.VPR and top-performing guide RNA candidates. These cells exhibit potent activation of proviral plasmids after transfection or after infection with AAV vectors delivering transgene cassettes carrying photoreceptor-specific promoters. In addition, we interrogated mechanisms to optimize this platform through the addition of multiple guide RNA sequences and co-expression of the universal adeno-associated virus receptor (AAVR). Collectively, this investigation identifies a rapid and broadly applicable strategy to enhance in vitro expression and to evaluate potency of AAV vectors that rely upon cell or tissue-specific regulatory elements.